2022
DOI: 10.1051/ro/2021188
|View full text |Cite
|
Sign up to set email alerts
|

Optimal inventory strategies for an imperfect production system with advertisement and price reliant demand under rework option for defectives

Abstract: Every industrial sector emits carbon emissions during production, which is always a major concern for environmental practitioners. To resolve this, innovative and smart ways are required that are not only cost-effective but also environmentally savvy. Moreover, the production processes are also prone to various imperfections, and thus the production of defectives is quite pragmatic. The handling of such defective products varies from industry to industry and type of products. The present study constructs an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The rate of production of these items or the total number of them can be decisive in EPQ inventory models. Guatam et al [16] determined the optimum production-inventory strategies for a flawed production system with price-reliant and advertisement demand under the rework option for defective items. Giri and Dash [17] derived an optimal batch shipment policy for a flawed production system with price, advertisement, and greensensitive demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rate of production of these items or the total number of them can be decisive in EPQ inventory models. Guatam et al [16] determined the optimum production-inventory strategies for a flawed production system with price-reliant and advertisement demand under the rework option for defective items. Giri and Dash [17] derived an optimal batch shipment policy for a flawed production system with price, advertisement, and greensensitive demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, Khanna et al [20] considered non-linear price-dependent demand for an inventory model with inspection error. In this direction, Gautam et al [12] developed an inventory model with price-dependent demand for defective items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They observed that customers are encouraged to acquire things when rebate marketing is used. According to Gautam et al (2022), manufacturers should invest more in advertisement in order to generate more profit and to increase demand. Hence, taking into account demand that is dependent on sales team efforts and selling price is more feasible in the case of production-inventory modelling.…”
Section: Literature Reviewmentioning
confidence: 99%